KARAKTERISTIK SIFAT KIMIA TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI KECAMATAN MALLUSETASI KABUPATEN BARRU - Junaidi, Sudirman; Putera, Muh. Ikbal; -, Harsani; Salim, Ade Putra (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
The research was conducted in the District Mallusetasi Barru which took place in April and August 2018. This study aims to know the characteristics of soil chemical properties in a variety of land use in the district Mallusetasi Barru. Decision 27 points samples taken at the study site using methodssurvey, using a map of land use resulting from Arc View GIS applications. The survey results produce primary data were then analyzed in the laboratory to determine the characteristics of soil chemical properties in District Mallusetasi Barru.Soil Chemical analysis carried out in the Laboratory of Chemistry and Soil Fertility Hasanuddin University, Makassar with the data analysis is the CEC, Soil pH, Magnesium (mg), Saturation bases, Potassium (K), Na, organic C (%) and Calcium (ca), The results of this study indicate thatchemical properties of Ca, Mg, K, Na, CEC, KB and C-Organic has a moderate to high criteria that affect the use of land in District Mallusetasi Barru